Dietary Copper Plays an Important Role in Maintaining Intestinal Barrier Integrity During Alcohol-Induced Liver Disease Through Regulation of the Intestinal HIF-1α Signaling Pathway and Oxidative Stress - Lin, Hongwei; Chen, Dazhi; Du, Qianjing; Pan, Tongtong; Tu, Hanxiao; Xu, Yuedong; Teng, Teng; Tu, Jingjing; Li, Ji; Lin, Zhuo; Wang, Xiaodong; Xu, Lanman; et al. (Frontiers in Physiology, 2020)
Impaired intestinal barrier function and oxidative stress injury play critical roles in the pathogenesis of alcoholic liver disease (ALD), and recent investigations have revealed a role for dietary copper in the liver and intestinal barrier function. Therefore, the current study investigates the mechanisms and role of dietary copper in alcohol induced liver diseases. C57BL/6 mice were used to create an alcoholic liver disease model with a Lieber-DeCarli diet containing 5% alcohol and were fed with different concentrations of dietary copper of adequate (6 ppm, CuA), marginal (1.5 ppm, CuM), or supplemental (20 ppm, CuS) amounts. Caco-2 cells were also exposed to ethanol and different concentrations of copper. Damages of the liver and intestine were evaluated by transaminases, histology staining, and protein and mRNA level, as well as cell proliferation, oxidative stress, and mitochondrial membrane potential. In animal experiments, the results indicate that an alcohol diet causes liver injury and disruption of intestinal barrier function as well as decreasing the expression of genes such as HIF-1α, occludin, SOD1, and GPX1. Supplemental dietary copper can revert these changes except for SOD1, but marginal dietary copper can worsen these changes. The in vitro cell experiments showed that proper copper supplementation can promote cell growth and reduce reactive oxygen species (ROS) production. In conclusion, supplemental dietary copper has beneficial effects on alcohol-induced intestine and liver injury, and marginal dietary copper shows detrimental effects on these parameters.